Asymmetric Induction in Darzens Condensation by Means of (R)-5,5- Dimethyl-4-Phenyloxazolidin-2-One as an Effective Chiral Auxiliary - Abed Badrian; Manouchehr Mamaghani; Khalil Tabatabaeian; Hassan Valizadeh (Letters in Organic Chemistry, 2007)
(R)-5,5-dimethyl-4-phenyloxazolidin-2-one 1 which is readily available from (R)-phenylglycine, was shown to be an effective chiral auxiliary for asymmetric Darzens reaction. It was employed in a simple and practical approach for the preparation of optically active glycidic esters.
Keywords: diastereoselectivity